2011
DOI: 10.1186/1471-2202-12-72
|View full text |Cite
|
Sign up to set email alerts
|

Errorless and errorful learning modulated by transcranial direct current stimulation

Abstract: BackgroundErrorless learning is advantageous over trial and error learning (errorful learning) as errors are avoided during learning resulting in increased memory performance. Errorful learning challenges the executive control system of memory processes as the erroneous items compete with the correct items during retrieval. The left dorsolateral prefrontal cortex (DLPFC) is a core region involved in this executive control system. Transcranial direct current stimulation (tDCS) can modify the excitability of und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 77 publications
2
34
0
4
Order By: Relevance
“…Recent fMRI and noninvasive brain stimulation research (Hammer, Mohammadi, Schmicker, Saliger, & Munte, 2011;Hammer, Tempelmann, Münte, 2013) suggests that healthy people recruit more prefrontal brain areas in errorful (memory) learning conditions when compared with errorless learning conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent fMRI and noninvasive brain stimulation research (Hammer, Mohammadi, Schmicker, Saliger, & Munte, 2011;Hammer, Tempelmann, Münte, 2013) suggests that healthy people recruit more prefrontal brain areas in errorful (memory) learning conditions when compared with errorless learning conditions.…”
Section: Introductionmentioning
confidence: 99%
“…suggests that the bilingual advantage in novel-word learning may be facilitated by enhanced executive control (see Bartolotti & Marian 2012;Bartolotti, Marian, Schroeder, & Shook, 2011;Kaushanskaya & Marian, 2009a, b), possibly reflecting the need to suppress erroneous responses (c.f., Hammer, Mohammadi, Schmicker, Saliger, & Münte, 2011;Warmington & Hitch, 2014;Warmington, Hitch, & Gathercole, 2013). More generally, executive control abilities have been shown to be a concurrent and longitudinal predictor of vocabulary development in monolinguals, and children and adolescents with specific language impairment show significant deficits in performing executive tasks (see Gathercole, 2006;Rose, Feldman, & Jankowski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The dorsolateral prefrontal cortex (DLPFC) is one of the most frequently targeted stimulation sites in tDCS studies. Studies have shown that tDCS has modulatory effects on attention (Gladwin et al 2012b;Kang et al 2009;Kang et al 2012;Nelson et al 2014;Nozari and Thompson-Schill 2013), memory and verbal processing (Fertonani et al 2010;Fertonani et al 2014;Metuki et al 2012;Sela et al 2012;Vannorsdall et al 2012;Wirth et al 2011), and executive functioning (including working memory; Andrews et al 2011;Berryhill and Jones 2012;Boggio and Khoury 2009;Boggio et al 2006;Dockery et al 2009;Filmer et al 2013;Fregni et al 2005;Gladwin et al 2012a;Hammer and Mohammadi 2011;Harty et al 2014;Hoy et al 2014;Jo et al 2009;Keshvari et al 2013;Leite et al 2011;Leite et al 2013;Mulquiney and Hoy 2011;Penolazzi et al 2010;Plewnia et al 2013;Saidmanesh et al 2012;Vanderhasselt et al 2013a;Vanderhasselt et al 2013b;Wu et al 2014;Zmigrod et al 2014); for a meta-analysis of the effects of tDCS on working memory, see Brunoni and Vanderhasselt (2014), among others.…”
Section: Introductionmentioning
confidence: 99%